Use of contrast media in computed tomography and magnetic resonance imaging in horses: Techniques, adverse events and opportunities. (22nd May 2017) - Nelson, B. B.; Goodrich, L. R.; Barrett, M. F.; Grinstaff, M. W.; Kawcak, C. E.
Summary: The use of contrast media in computed tomography (CT) and magnetic resonance imaging (MRI) is increasing in horses. These contrast‐enhanced imaging techniques provide improved tissue delineation and evaluation, thereby expanding diagnostic capabilities. While generally considered safe, not all contrast media exhibit the same safety profiles. The safety of contrast media use and descriptions of adverse events occurring in horses are sparsely reported. This review summarises the reported evidence of contrast media use and adverse events that occur in horses, with added contribution from other veterinary species and studies in man for comparison. This comprehensive data set empowers equine clinicians to develop use and monitoring strategies when working with contrast media. Finally, it summarises the current state‐of‐the‐art and highlights the potential applications of contrast‐enhanced CT and MRI for assessment of diseased or injured equine tissues, as well as (patho)physiological processes.